2014
DOI: 10.7448/ias.17.1.18808
|View full text |Cite
|
Sign up to set email alerts
|

High HIV incidence in the postpartum period sustains vertical transmission in settings with generalized epidemics: a cohort study in Southern Mozambique

Abstract: IntroductionAcute infection with HIV in the postpartum period results in a high risk of vertical transmission through breastfeeding. A study was done to determine the HIV incidence rate and associated risk factors among postpartum women in Southern Mozambique, where HIV prevalence among pregnant women is 21%.MethodsA prospective cohort study was conducted in six rural health facilities in Gaza and Maputo provinces from March 2008 to July 2011. A total of 1221 women who were HIV-negative on testing at delivery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 16 publications
(19 reference statements)
3
45
2
Order By: Relevance
“…A large prospective study of postpartum women in southern Mozambique also found a substantial HIV incidence rate of 3.2 per 100 WY overall, highest in the youngest women of 18–19 years [5]. The incidence rate among participants in that study from Gaza Province, where Chókwè is located, was slightly higher at 3.6 per 100 WY.…”
Section: Discussionmentioning
confidence: 83%
“…A large prospective study of postpartum women in southern Mozambique also found a substantial HIV incidence rate of 3.2 per 100 WY overall, highest in the youngest women of 18–19 years [5]. The incidence rate among participants in that study from Gaza Province, where Chókwè is located, was slightly higher at 3.6 per 100 WY.…”
Section: Discussionmentioning
confidence: 83%
“…Longitudinal HIV incidence data is limited in Mozambique with approximately five reported studies across the country [13,17,2022]. Incidence data among women has been reported in post-partum clinics at 2.9 per 100 person-years in Maputo Province and at 3.6 in Gaza Province, at 4.6 in a cohort study in Gaza, at 4.9 from cross-sectional surveys in Manhiça, at 6.5 in a cohort study in Sofala, and as high as 14.1 based on consecutive prevalence surveys in Manhiça [13,17,2022].…”
Section: Discussionmentioning
confidence: 99%
“…Incidence data among women has been reported in post-partum clinics at 2.9 per 100 person-years in Maputo Province and at 3.6 in Gaza Province, at 4.6 in a cohort study in Gaza, at 4.9 from cross-sectional surveys in Manhiça, at 6.5 in a cohort study in Sofala, and as high as 14.1 based on consecutive prevalence surveys in Manhiça [13,17,2022]. Participants were similar across the studies, as sexually active women of reproductive age, although with the exception of the latter referenced study in Manhiça, women in the other studies tended to be slightly younger than in our study with mean ages below the mid-20s, more comparable to the Mavalane than the Manhiça cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Service integration of HEI screening into immunization clinics has previously been shown to be associated with increased uptake, younger age at screening, increased receipt of test results, and increased enrollment in HIV care. 38 Further, the high HIV incidence among postpartum women in Mozambique 39 and the higher risk of viral rebound in the first 3 40 to 6 41 months postpartum highlights the importance of engaging postpartum women in ongoing care to preserve the mother’s health and to prevent vertical transmission, including counseling on appropriate feeding, HEI screening, and prevention of future unplanned pregnancies.…”
Section: Discussionmentioning
confidence: 99%